Estimation and analysis of Thai national freight demands from GPS data - Siripirote, Treerapot; Sumalee, Agachai; Ho, H. W.; Chankaew, Nattaphon; Jedwanna, Krit (My University, 2018)
Freight transport has been increased in both demand and distance travelled in recent years due to the changes in consumer purchasing patterns and the improvements in the transportation systems. Such increases cause serious adverse impacts on traffic conditions and air qualities. This paper proposes a framework that make use of passively collected truck Global Positioning System (GPS) data and link counts in the estimation of national freight demands, which are the crucial quantities in the design of management and remedial measures. Effective truck stops and the corresponding activities will be determined from the GPS data and used in estimating the observed freight demands. Such observed demands will be used with the link counts to determine the national freight demands. An empirical example from Thailand is adopted in this paper to illustrate the proposed framework in estimating the national freight demands from GPS data and link counts.
Keywords: Freight transport; Global position system; Origin-destination estimation; Truck activity